O clima urbano de Rancharia (SP) - Teixeira, Danielle Cardozo Frasca [UNESP] (2015)
Urban environmental problems are increasingly associated with the transformation of landscapes, which is seen in the decrease of environmental quality and quality of life on the part of city dwellers. Even small and mid-sized cities are subject to alterations, especially those referring to the atmospheric environment. Besides that, small and mid-sized cities have been adding quantitative representation in the setting of Brazilian de-metropolization (SANTOS, 1991). Thus, the intention is to analyze the urban environmental quality of Rancharia, a small city in the state of São Paulo, with the urban climate as the main reference, especially the thermal-hygrometric field based on the theoretical proposal by Monteiro (1976), and also adapting to the methodological proposals by Mendonça (1994) and Amorim (2000). Rancharia is a small city, a tourist resort town that attracts tourists and water sport enthusiasts. For this study, the delimited subsystem is thermodynamic, perceived by the thermal comfort canal with direct impacts on human performance. The characterization of the urban soil use and occupation standards will be done first, differentiating types of use and identifying the occurrence of green areas by obtaining satellite images and from field studies. Then, data collection of temperature and relative humidity is projected in urban areas, rural areas and the area surrounding the water resort based on fixed weather stations and mobile transects on representative days in the winter and summer...